RETRACTED: Long-term follow-up after abdominal cerclage: A population-based cohort study. (March 2017) - Sneider, Kirstine; Christiansen, Ole Bjarne; Sundtoft, Iben Blaabjerg; Langhoff-Roos, Jens
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of the Editor-in-Chief and the Authors as the Authors failed to request and receive permission to use the data from Aarhus Hospital.